Amoeba-like self-oscillating polymeric fluids with autonomous sol-gel transition - Michika Onoda (Nature Portfolio, 2017)
Most polymeric materials that show sol-gel transitions are unidirectional and stimuli-responsive systems. Here the authors show a block copolymer solution that undergoes autonomous and periodic sol-gel transitions under constant conditions.